2010
DOI: 10.1111/j.1464-0597.2010.00433.x
|View full text |Cite
|
Sign up to set email alerts
|

Work-Home Interaction and Psychological Strain: The Moderating Role of Sleep Quality

Abstract: Sleep has been considered crucial for recovery, but little is known about the specific associations between the work-family interface and sleep quality. Based on COR theory, the goal of this study is to examine the moderating role of sleep quality on the relationship between work-home interaction (i.e. negative work-home interaction, negative home-work interaction, positive workhome interaction, and positive home-work interaction) and psychological strain. A total of 273 ambulance workers from Spain participat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 65 publications
1
9
0
1
Order By: Relevance
“…Second, our main focus is to examine whether sleep disturbance acts as moderator of the effect of CMCs on depressive symptoms. This aim is in line with studies which have shown a moderating impact of sleep on various risk factors in association with depression and psychological strain, and extends prior work which has looked at the main effects of CMCs and sleep disturbance on depression by considering potential moderation (Leggett, Burgard, & Zivin, 2016; Sanz‐Vergel, Demerouti, Mayo, & Moreno‐Jiménez, 2011). Finally as a second aim we consider whether there is an interaction between age and an individual’s variability in CMCs in association with depressive symptoms.…”
Section: Age and Illnesssupporting
confidence: 81%
“…Second, our main focus is to examine whether sleep disturbance acts as moderator of the effect of CMCs on depressive symptoms. This aim is in line with studies which have shown a moderating impact of sleep on various risk factors in association with depression and psychological strain, and extends prior work which has looked at the main effects of CMCs and sleep disturbance on depression by considering potential moderation (Leggett, Burgard, & Zivin, 2016; Sanz‐Vergel, Demerouti, Mayo, & Moreno‐Jiménez, 2011). Finally as a second aim we consider whether there is an interaction between age and an individual’s variability in CMCs in association with depressive symptoms.…”
Section: Age and Illnesssupporting
confidence: 81%
“…It is also possible that a good night's sleep is sufficient to recover with no negative effects on burnout symptoms in the morning as a result. However, Sanz‐Vergel, Demerouti, Mayo, and Moreno‐Jimenez () examined the moderating impact of sleep quality on the relation between WHI and psychological strain and did not find any evidence for a moderating effect. Therefore, it is important that future studies establish the temporal order of the model variables by assessing the variables at different points in time during the day.…”
Section: Discussionmentioning
confidence: 99%
“…Jako wspólne bariery nasilające oba konflikty wymienia się liczbę godzin pracy, presję w pracy (5,6), ograniczenia organizacyjne, krytykanctwo, niezgodę w rodzinie i neurotyczność (4). Wysoki poziom konfliktów wiąże się pozytywnie z wypaleniem zawodowym (2,7), negatywnie z satysfakcją z pracy (5,8) i pozytywnie z napięciem psychologicznym (9). Każdy z konfliktów ma jednak odmienne uwarunkowania, specyficzne przyczyny i następstwa (2,10,11).…”
unclassified